The relationship between human behavior and stock returns in efficient stock markets: the mood-effect under a cultural perspective - Senarathne, Chamil W.; Jianguo, Wei (Związek pomiędzy ludzkim zachowaniem a zwrotem z akcji na efektywnych giełdach: efekt nastrojów w perspektywie kulturowej, 2019)
This paper examines the relationship between stock return and human behavior in ten well-established stock exchanges, from a monthly data sample from January 1991 to December 2015. The results show that there is no sufficient evidence to generalize the impact of human behaviour on common stock return, through mood state altered by weather variables. When the substance of the underlying process (i.e. the weather alters the mood state) is established by logit regression, the results reveal that there is a bias in the variable selection as regressors, which is subject to the metrological situation of each country (or region). As such, collectivism does not appear to be an explanatory variable of the magnitude of price changes, as a variable uncontrolled for in the regression. Although the null hypothesis is accepted for four countries in the sample, the findings do not warrant researchers to generalize the effect of human behavior on stock price changes through weather variables, for a large population
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 2, s. 207-220
Keywords: efficient markets; stock returns; culture; weather variables; OLS regression; logit regression; efektywne rynki; zwrot z akcji; kultura; zmienne pogodowe; regresja OLS; regresja logitowa